2023
DOI: 10.3390/ijms24076492
|View full text |Cite
|
Sign up to set email alerts
|

The Hypothalamic-Pituitary-Gonadal Axis in Men with Schizophrenia

Abstract: Schizophrenia is a severe mental disorder with a chronic, progressive course. The etiology of this condition is linked to the interactions of multiple genes and environmental factors. The earlier age of onset of schizophrenia, the higher frequency of negative symptoms in the clinical presentation, and the poorer response to antipsychotic treatment in men compared to women suggests the involvement of sex hormones in these processes. This article aims to draw attention to the possible relationship between testos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 221 publications
0
2
0
Order By: Relevance
“…The differential spliceosome of TAC1 can produce two isoforms, which encode tachykinins that regulate prolactin (PRL) release ( Pan et al, 2021 ). Increased PRL interferes with the hypothalamus’ secretion of GnRH, leading to decreased pituitary secretion of LH and FSH ( Matuszewska et al, 2023 ). In our study, we found that lncRNAs (ENSCHIT00000010293, ENSCHIT00000010304, ENSCHIT00000010306, ENSCHIT00000010290, and ENSCHIT00000010298) may act through cis-targeted regulation to regulate TAC1.…”
Section: Discussionmentioning
confidence: 99%
“…The differential spliceosome of TAC1 can produce two isoforms, which encode tachykinins that regulate prolactin (PRL) release ( Pan et al, 2021 ). Increased PRL interferes with the hypothalamus’ secretion of GnRH, leading to decreased pituitary secretion of LH and FSH ( Matuszewska et al, 2023 ). In our study, we found that lncRNAs (ENSCHIT00000010293, ENSCHIT00000010304, ENSCHIT00000010306, ENSCHIT00000010290, and ENSCHIT00000010298) may act through cis-targeted regulation to regulate TAC1.…”
Section: Discussionmentioning
confidence: 99%
“…However, the exact pathophysiology of endocrine disturbances in demyelination diseases and the involvement of the HPG axis is still poorly understood (4). The testosterone level is regulated by endocrine interactions between the hypothalamus, anterior pituitary gland, and testis (6). The responsible neurons for gonadotropin-releasing hormone (GnRH) secretion frequently concentrate in the arcuate nucleus of the hypothalamus (7).…”
Section: Introductionmentioning
confidence: 99%